2016
DOI: 10.1093/annhyg/mew004
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chemical Pesticides in Ethiopia: A Cross-Sectional Comparative Study on Knowledge, Attitude and Practice of Farmers and Farm Workers in Three Farming Systems

Abstract: Chemical pesticides, regardless of their inherent hazard, are used intensively in the fast changing agricultural sector of Ethiopia. We conducted a cross-sectional pesticide Knowledge, Attitude and Practice (KAP) survey among 601 farmers and farm workers (applicators and re-entry workers) in three farming systems [large-scale closed greenhouses (LSGH), large-scale open farms (LSOF), and small-scale irrigated farms (SSIF)]. Main observations were that 85% of workers did not attain any pesticide-related training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
138
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 15 publications
17
138
4
Order By: Relevance
“…There is a large amount of case study research conducted on knowledge, attitudes, perception and unsafe use of pesticides among farmers in Africa (Williamson, 2008(Williamson, , 2011Damite & Tabor, 2015;Negatu et al, 2016;PAN Africa, 2008), Asia (Hoi et al, 2010(Hoi et al, , 2013Jin et al, 2015;Panuwet et al, 2012) and Latin America (Jansen, 2003(Jansen, , 2008Rios-Gonzalez et al, 2013). However, none of these studies applied a sector governance analysis approach for making the use of pesticides visible through and across registration, importation, distribution, use and interaction of the three key pesticide actors (state (regulator), traders (business) and users (farmers)).…”
Section: Governance Of Pesticide Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a large amount of case study research conducted on knowledge, attitudes, perception and unsafe use of pesticides among farmers in Africa (Williamson, 2008(Williamson, , 2011Damite & Tabor, 2015;Negatu et al, 2016;PAN Africa, 2008), Asia (Hoi et al, 2010(Hoi et al, , 2013Jin et al, 2015;Panuwet et al, 2012) and Latin America (Jansen, 2003(Jansen, , 2008Rios-Gonzalez et al, 2013). However, none of these studies applied a sector governance analysis approach for making the use of pesticides visible through and across registration, importation, distribution, use and interaction of the three key pesticide actors (state (regulator), traders (business) and users (farmers)).…”
Section: Governance Of Pesticide Problemsmentioning
confidence: 99%
“…Scenarios for the future use of seven selected pesticides indicated that agricultural use of chlorothalonil, deltamethrin, endosulfan and malathion in some crops may result in medium to high risks to aquatic species in the Ethiopian context (Teklu et al, 2015). In addition, Negatu et al (2016) report a large increase in pesticide usage intensity, illegitimate usages of DDT and Endosulfan on food crops and direct import of pesticides without passing through the formal Ethiopian registration process. Moreover, Gebremichael et al (2013) report the presence of DDT from their analysis of organochlorine pesticide residues in human and cow's milk in Southwestern Ethiopia.…”
Section: Challenges To Pesticide Registration Distribution and Use Imentioning
confidence: 99%
See 1 more Smart Citation
“…However, pesticide use practices by small-scale farmers in Ethiopia often violate recommendations like the use of safe storage facilities, complying with health and safety instructions, using protective devices when applying pesticides, and safe disposal of pesticide containers (Negatu et al, 2016;Mengistie et al, 2016). Similarly, large-scale production agriculture, including the horticultural and flower farms, also fails to adhere to international safety standards for the environmental and for workers (Mengistie et al, 2014).…”
Section: Comparison Of Endosulfan As a Detected Ocp And As Model Predmentioning
confidence: 99%
“…In addition to the present PhD project, two more PhD projects have been initiated under this programme. One focusses on environmental policy and governance issues associated with pesticides in Ethiopia (Mengistie et al, 2014; while the other focuses on the overall health impacts of pesticides in Ethiopia (Negatu et al, 2016). A general description of the PRRP programme is provided in the Introduction to this thesis, and on (http://www.prrp-ethiopia.org/).…”
Section: Comparison Of Endosulfan As a Detected Ocp And As Model Predmentioning
confidence: 99%